What's the difference? Using descriptors to classify the care provided to children and adolescents with behavioral and emotional problems. (February 2016) - Evenboer, K.E.; Huyghen, A.M.N.; Tuinstra, J.; Knorth, E.J.; Reijneveld, S.A.
Abstract: More detailed information concerning the content of interventions for children with behavioral and emotional problems may help to improve their effectiveness. In this study, we made a distinction between "well-defined" and "poorly defined" interventions that were being provided in a catchment area. Well-defined interventions are included in the Dutch "Effective Youth Interventions" (EYI) database; poorly defined interventions are not. We aimed to assess (1) to what extent "well-defined" interventions had similar content, that is, could be grouped together, and (2) whether the proportion of those interventions that could be grouped was smaller for "well-defined" than for "poorly defined" interventions. The interventions were scored by professionals in terms of the degree to which the activities entailed in that intervention were covered by the 20 descriptors that represent that specific type of care. Those interventions with similar scores on descriptors were then grouped together. The percentage of interventions that could be grouped was then compared with that found in an earlier, comparable study concerning "poorly defined" interventions. "Well-defined" interventions could be classified into 19 groups; this represented a reduction in interventions of 44%, with the largest reduction found in those interventions within the main types "individual child support" and "family support." This reduction was somewhat smaller than for the "poorly defined" interventions (52%), where the largest reduction was found in the main type "family support." The descriptors then allowed interventions offered to children to be grouped within and across care organizations. In this way, we were further able to distinguish differences and similarities in the content of grouped interventions per main type of support. Highlights: Number of interventions for youth with psychosocial problems increased enormously. Research on the content is needed in order to make statements on the effectiveness. Interventions included in the study show substantially overlapping content. Descriptors allowed interventions to be grouped within and across organizations. Application of ingredients differs per target group and aim of the intervention.